PENERAPAN VIDEO PEMBELAJARAN NAIL ART MELALUI MEDIA SOSIAL TIKTOK PADA MATA PELAJARAN RIAS WAJAH KONSENTRASI KEAHLIAN XI TKKR SMKN 1 BUDURAN - Meylandini, Ajeng Eka; Dwiyanti, Sri; Mutimmatul Faidah; Kusstianti, Nia (Program Studi Pendidikan Tata Rias, 2026)
The integration of digital technology in vocational education has become increasingly essential, particularly in practical learning that requires clear visualization of work procedures. This study aimed to examine the feasibility of Nail Art instructional videos developed through the TikTok social media platform, analyze improvements in students’ cognitive learning outcomes, and identify students’ responses to the implementation of the media in the hand and foot care competency at SMKN 1 Buduran. This research employed a quantitative approach using a pre-experimental One Group Pretest–Posttest design. The research subjects consisted of 36 eleventh-grade students of the Beauty Education program. The research instruments included expert validation sheets to assess media feasibility, pretest and posttest to measure cognitive learning outcomes, and student response questionnaires. The results showed that the TikTok-based Nail Art instructional video was categorized as highly feasible, with an average score of 4.67. Students’ cognitive learning outcomes improved significantly, as indicated by an average posttest score of 84.6, with all students achieving learning mastery. Statistical analysis revealed a significance value of 0.000 (p < 0.05), indicating a significant difference in learning outcomes before and after the use of the instructional media. Furthermore, students’ responses to the TikTok-based learning media were classified as very positive, with a response rate exceeding 95%. These findings indicate that TikTok-based Nail Art instructional videos are feasible and effective as innovative learning media to enhance learning outcomes and student engagement in vocational practical learning. Keywords: learning video, TikTok, Nail Art, learning outcomes, vocational education